2019
DOI: 10.18823/asiatefl.2019.16.4.12.1251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flipped Classroom on High- and Low-achievers’ English Vocabulary Learning

Abstract: The flipped classroom, an approach that extends learning beyond the classroom, has been extensively and empirically researched in the science and math disciplines. However, whether the flipped classroom is feasible in senior high school education-where variation in student performance is of particular concern-has yet to be examined. In this light, this study set out to verify the feasibility and effectiveness of the flipped classroom in high school education, and to compare its effects with conventional lectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The 362 FCM based studies involved different methodologies the analysis of which explored that the documents distributed on FLM in education, within the range of ten years (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), mostly employed mixed-methods research design (f=178, %=49.17), followed by a quantitative research design (f=121, %=33.43). The analysis of research design revealed that multiple tools were utilized to collect in-depth information revealing the effectiveness of the FCM (e.g., Bouwmeester et al, 2019;Burns et al, 2019;Finkenberg & Trefzger, 2019;Halasa et al, 2019;Jitjumnong & Suksakulchai, 2019;Parra-Gonzalez et al, 2020;Wang & Zhu, 2019;Yang et al, 2019;Zamora-Polo et al, 2019). The tools utilized in gathering the required data were mainly surveys, questionnaires, observations, interviews and field notes.…”
Section: Methodsmentioning
confidence: 99%
“…The 362 FCM based studies involved different methodologies the analysis of which explored that the documents distributed on FLM in education, within the range of ten years (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), mostly employed mixed-methods research design (f=178, %=49.17), followed by a quantitative research design (f=121, %=33.43). The analysis of research design revealed that multiple tools were utilized to collect in-depth information revealing the effectiveness of the FCM (e.g., Bouwmeester et al, 2019;Burns et al, 2019;Finkenberg & Trefzger, 2019;Halasa et al, 2019;Jitjumnong & Suksakulchai, 2019;Parra-Gonzalez et al, 2020;Wang & Zhu, 2019;Yang et al, 2019;Zamora-Polo et al, 2019). The tools utilized in gathering the required data were mainly surveys, questionnaires, observations, interviews and field notes.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the studies (n = 12) were grounded on the scheme of constructivism (Yu & Gao, 2022;Zhonggen, 2019;Cabi, 2018;Bonyadi, 2018;Yang et al, 2019;Vaezi et al 2019;Zainuddin et al, 2019;Abdullah et al, 2019B, Chen & Liu, 2019Liu & Zhang, 2018;Li & Qu, 2019). Constructivists believe that learners build their own knowledge by integrating new information with their pre-existing knowledge instead of obtaining information passively.…”
Section: Theoretical Framework In the Previous Studiesmentioning
confidence: 99%
“…For instance, a study by Yang et al (2019) was conducted based on the F-L-I-P™ principle. This principle emphasizes the need for flexibility in the learning environment, self-directness in learning, qualified learning materials, and the professionalism of the educators.…”
Section: Theoretical Framework In the Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations